Devolving authority: public secondary schools’ perception and response to school-based management policy in Indonesia - Sumintono, Bambang (Ministry of Education and Culture, Republic of Indonesia, 2012)
In the post New Order Indonesia (from 1998) ideas about school based management in the education sector have become increasingly popular. One of the characteristics of this is devolving authority to the school level at least in three areas: staff, curriculum and budget. Using qualitative inquiry, the researchers collected data from schools and district level stakeholders in Mataram through questionnaire, interview, observation and document analysis to reveal their perception about devolving authority issues. It is found that the school started exercising some authorities that were previously in their superior officers’ control, however some previous practices still conducted in conjunction with the school committees.